A new concept of Tectaria taccifolia (fee) price (aspidiaceae) a polymorphous Philippine fern - Salgado, A.E (1988)
The concept of Tectaria taccifolia (Fee) Price is hereby expanded to include the polymorphous Tectaria hilocarpa (Fee) Price. Characters used to distinguish Hemigramma from Tectaria are discussed in the light of field observations.